2017
DOI: 10.1097/jcn.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Symptoms Are Associated With Abnormal Endothelial Function

Abstract: Background Insomnia is a prevalent sleep disorder and it has been increasingly associated with cardiovascular morbidity and mortality. The reasons for this relationship are not completely understood but may involve endothelial dysfunction. In this study, we hypothesized that insomnia symptoms would be associated with reduced endothelial function. Methods Working adults [n=496, 67.5% female, 78.6% white, mean age: 48.7±10.8 years, body mass index (BMI): 28.2±6.7 kg/m2, diabetes: 5.8%, hypertension: 20.0%, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Both exercise and stress management training have been shown to produce favorable changes in physiological regulatory systems, including improved vascular endothelial vasodilatory function. 19 Interestingly, impaired endothelial function has been linked both to nighttime hypertension and insomnia 31, 32 . Although exercise did not result in improved heart rate variability (HRV) measured during supine deep breathing, stress management training did improve HRV compared to Usual Care.…”
Section: Discussionmentioning
confidence: 99%
“…Both exercise and stress management training have been shown to produce favorable changes in physiological regulatory systems, including improved vascular endothelial vasodilatory function. 19 Interestingly, impaired endothelial function has been linked both to nighttime hypertension and insomnia 31, 32 . Although exercise did not result in improved heart rate variability (HRV) measured during supine deep breathing, stress management training did improve HRV compared to Usual Care.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue, daytime sleepiness, mood disturbance, decreased performance, and cognitive impairment induced by poor sleep [ 13 - 15 ] can affect quality of life negatively [ 16 , 17 ]. Moreover, there is a relationship between sleep disorders and morbidity rates of various diseases such as hypertension [ 18 ], diabetes mellitus [ 19 , 20 ], atherosclerosis [ 21 ], cardiovascular disease [ 22 , 23 ], dementia [ 24 ], and depression [ 25 ]. Also, not only morbidity but even mortality has been reported in patients with sleep disorder [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data have shown that longterm insomnia will cause increased morbidity rates of many disease such as heart diseases, hypertension, hyperlipidemia, senile dementia, depression, and anxiety. Therefore [2], the 2 Evidence-Based Complementary and Alternative Medicine effective prevention and treatment of insomnia is still one of the global concerns [3].…”
Section: Introductionmentioning
confidence: 99%